Analysis of The Implementation of Electronic Medical Records At Rsi Fatimah Banyuwangi - Syahrul Akbar; Setya Haksama; Musa Ghufron (CV. Inara, 2025)
The implementation of Electronic Medical Records (EMR) at Fatimah Islamic Hospital Banyuwangi (RSI Fatimah Banyuwangi) is part of an important digital transformation in improving the quality of health services. This study aims to analyze the factors that influence the implementation of EMR, as well as to identify challenges and potential improvements in its implementation. This study uses a quantitative approach with an explanatory research design and multiple linear regression analysis to test the influence of factors such as acceptability, adoption, feasibility, fidelity, implementation cost, coverage, and sustainability on the implementation of EMR. The results show that all factors tested have a significant effect on the successful implementation of RME. Among these factors, coverage has the greatest influence with a regression coefficient of 0.995, followed by sustainability and feasibility. In addition, acceptability and adoption are also proven to contribute positively to the effectiveness of RME implementation. Although the implementation of EMR at RSI Fatimah Banyuwangi has been running well, challenges related to technical support, system sustainability, and expansion of EMR usage throughout all hospital units still need to be addressed. This study provides practical recommendations to improve technological infrastructure, enhance staff training, and ensure the maintenance and continuous updating of the EMR system.